METHODOLOGY TO DESIGN PROFESSIONAL COMPETENCES IN THE FIELD OF OIL AND GAS INDUSTRY - O. V. Brusnik; E. A. Muratova (Высшее образование в России)
The article addresses the issues in the sphere ofoil and gas education. The authors propose an integrated methodical employer oriented system for oil and gas education. This is a problem-based educational model implementing innovative educational technologies for organization the real and virtual communication space for students and lecturers. The model uses active and interactive learning methods such as business games, round table discussions, brain storms, case study and others. An important element of the proposed educational system is an assessment toolkit including a set of typical tasks, tests, which feature the close connection with the special needs of employers. One of the final assessment tests in this model is an interdisciplinary examination, which since 2016 is being held in online test format in Tomsk Polytechnic University (180-minute standardized exam). The implementation of the innovative model implies creating of new centres for formation gruaduates'professional competences in oil and gas sphere. These centres will provide conditions for students' activities in engineering organizations with an expert support. According to CDIO standards these centres will also provide so called "social" education. On the whole the proposed model of innovative oil and gas education enables to reduce the disbalance between the demands of oil and gas companies to graduates and the currently performed education program "Oil and gas business."